Pemrograman Web Membuat Sisten Informasi Akademik Sekolah dengan PHP-MYSQL & DRAEMWEAVER - NUGROHO, Bunafit (Gava Media, 2014)
Pemrograman Web Membuat Sisten Informasi Akademik Sekolah dengan PHP-MYSQL & DRAEMWEAVER